Platelet membrane-modified catalase/silica nanoparticles inhibit radiation infection - XIONG Tainong; LI Chenwenya; CHEN Yin (陆军军医大学学报)
Objective‍　‍To provide an effective strategy for the prevention and treatment of radiation-induced infections by preparing platelet membrane-modified catalase/silica nanoparticles (PCNP) capable of targeting leukocytes. Methods‍　‍PCNP and catalase/silica nanoparticles (CNP) were prepared by using platelet membrane, catalase (CAT) and silica, and its biological safety was preliminarily evaluated with cell survival test, hemolysis test and acute toxicity test in mice after tail vein administration; The culture medium, FITC labeled (FITC+) PCNP and FITC labeled (FITC+) CNP were co-incubated with human peripheral blood B lymphocytes (AHH-1) and mouse monocyte macrophages (RAW264.7), respectively. Thus, there were control group, FITC+ PCNP group and FITC+ CNP group of AHH-1 and RAW264.7 cells. Laser confocal microscopy was used to observe the intracellular fluorescence intensity of PCNP to evaluate the leukocytes targeting function. AHH-1 cells were divided into control, irradiation, platelet membrane, CNP (100 μg/mL) and PCNP (100 μg/mL) groups. After corresponding co-incubation, the cell media were exposed to6 Gy Co60 γ irradiation. The generation of reactive oxygen species (ROS) and cell apoptosis were measured to determine the effect of nanoparticles on reducing radiation injury of leukocytes. Twenty C57BL/6 male mice (weighing 18~20 g) were randomly divided into irradiation group (n=10) and 10 mg/kg PCNP group (n=10). In 2 h after corresponding agents were injected into the mice through tail vein, the mice received whole-body irradiation of 5 Gy Co60 γ ray, and then in 2 h later, they were given intraperitoneal injection of multidrug resistant Acinetobacter baumannii (MDR-AB). The infection inhibitory effect of PCNP after irradiation was evaluated by detecting the bacterial load in main organs. Results‍　‍The hydration particle of PCNP is 91.3 nm in size, and does not exhibit significant cytotoxicity or hemolytic toxicity at concentrations <400 µg/mL. Intravenous injection of 20 mg/kg PCNP resulted in normal increase in the body weight but no obvious pathological changes in the major organs such as the heart, liver, spleen, lungs, and kidneys. In AHH-1 and RAW264.7 cells, PCNP showed significant advantages in targeting compared to the FITC+ CNP group [(15.45±3.48)% vs (9.33±2.03)%, P<0.01; (11.25±2.08)% vs (7.06±0.71)%, P<0.001]. PCNP also effectively reduced the generation of ROS [(22.73±3.71)% vs (60.90±9.08)%, P<0.001] and apoptotic rate [(9.84±0.92)% vs (38.96±3.62)%, P<0.001] in AHH-1 cells. In in vitro study, bacterial colonization after irradiation showed that there was significantly less MDR-AB colonies in the spleen of mice intervened with PCNP than those of the irradiation group [(17.50±1.38)×104 vs (13.20±2.29)×106 CFU/g, P<0.001]. Conclusion‍　‍PCNP can effectively inhibit the complications of radiation infection in mice, which is due to its direct protective effect on leukocytes.